The impact of the use of electronic technology on the effectiveness of the stages of the external audit process in the city of Tripoli (Economic studies journal, 2021)
The impact of the use of electronic technology on the effectiveness of the stages of the external audit process in the city of Tripoli Abstract:The main objective of this study is to identify the impact of the use of electronic technology on the effectiveness of the stages of the external audit process (planning, documentation, control) from the point of view of the external auditors in the city of Tripoli. Preliminary and statistical information from the study sample, where (142) forms were distributed to a sample of audit offices in the city of Tripoli, and after giving the participants a sufficient period to answer the questions of the questionnaire, (121) of the distributed forms were received. The study reached several results, the most important of which are: There is a statistically significant effect of the use of electronic technology on the effectiveness of the stages of the audit process from the point of view of the Libyan external auditors, and based on the results of the study, the researcher recommended the need to keep pace with technological developments and pursue modern systems in the areas of auditing and internal control systems, and training auditors by raising their efficiency. It is necessary to constantly work on developing the techniques that audit offices follow when reviewing data processing systems, and then reconsidering the design of traditional audit programs when examining the accounts of companies that use electronic means in accounting, and amending them from time to time to suit new circumstances.
Keywords: electronic technology; External Auditing; Auditing; Elmergib University